A comparison of the effect of organic acids and dicalcium phosphate supplementation on phosphorus bioavailability, growth performance and digestive enzyme activities of Labeo rohita fingerlings. (18th October 2020) - Javid, Iqra; Fatima, Mahroze; Shah, Syed Zakir Hussain; Afzal, Muhammad
Abstract: The effect of organic acids (OA) and dicalcium phosphate (Pi ) supplementation in the feed of Labeo rohita fingerlings was studied by formulating seven practical diets, designed as D1 with no feed additives {dicalcium phosphorus (Pi) and organic acid (OA) blend} while, D2, D3, D4 and D5 were supplemented with Pi at the graded levels of 5, 10, 15 and 20 g/kg, respectively, whereas D6 and D7 contained blend of OA at 15 and 30 g/kg, respectively. The diet supplemented with OA blend exhibited increase ( p  < .05) in growth of L. rohita fingerlings compared with the diet supplemented with Pi . The OA supplementation at both levels showed significant improvement in nutrients digestibility and minerals absorption in fingerlings. Moreover, in case of muscle proximate composition, crude fat (CF) and crude protein (CP) were increased ( p  < .05) with the inclusion of OA blend in the diet while crude ash (CA) was improved by Pi supplementation. Additionally, digestive enzyme activities were not affected ( p  ˃ .05) by OA blend supplementation while increased activities were observed in the fingerlings fed with Pi diet. Consequently, supplementation of OA blend in the diet improved the growth performance and nutrient status while Pi enhanced digestive enzyme activities of L. rohita fingerlings.